Optimization of Process Parameters for Bioethanol Production from Low grade Iraqi Dates - Flayeh, Hussain Majeed (Al-Nahrain Journal for Engineering Sciences, 2017)
Box-Wilson experimental design method was employed to optimize bioethanol production from low grade, unclassified, waste Iraqi dates. The optimization process was based on four independent relevant parameters-initial sugar concentration (50-100 g/l), pH (4.5-6.5), fermentation time (48-96 hrs), and temperature (25-35?). A maximum bioethanol yield of 33.9 g/l was practically achieved following thirty different experimental runs, as specified by 24-Central Composite Design (CCD). The optimum values for the aforementioned four parameters, corresponding to the maximum yield, were: 75g/l, pH 5.5, 72 hrs, 30?, respectively. The obtained experimental data were utilized to develop a semi-empirical model, based on a second-degree polynomial, to predict bioethanol yield. The model was tested using ANOVA software (Design expert® 9) and found acceptable (R2=0.9025). Yield response surface and contour plots were created using the developed model, which revealed the presence of high-yield plateaus whose specifications will be useful in controlling pilot-or industrial scale future units to ensure economical feasibility.